Analisis Kesalahan Berbahasa Dalam Surat Korespondensi Bisnis Politeknik Negeri Manado - Sinaga, Floren Agnesia (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Language as a communication tool that do not adhere to the rules and used continuously will result in an increasing number of errors due to a decreasing awareness of the mistakes. By the time, people may come to believe that error is correct. To response this problem, identifying language errors must be done early in education process to prevent these mistakes into the professional career. The aim of this study is to analyze the language error in business letter in business correspondence course at Manado State Polytechnic. The research focuses on two types of language errors in the business letters, they are: spelling errors and errors in the use of effective sentence. A qualitative descriptive method was used with 25 business letters which were written by the students. The results revealed a total of 101 errors occurred in the letters. There were 56 spelling errors and 45 errors related to effective sentence used. The most frequent spelling errors were found in the use of capital letters while involved redundancy and inappropriate diction in effective sentence errors. This study is expected to raise awareness of the importance of using proper and correct Indonesian language rules to improve written communication skills in the professional world. Keywords: Language Errors, Business Letters, Business Correspondence